2020
DOI: 10.1136/bmjopen-2019-036549
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain and rate of late-onset preeclampsia: a retrospective analysis on 57 000 singleton pregnancies in Reunion Island

Abstract: ObjectivesTo investigate in singleton term pregnancies (≥37 weeks gestation) if applying optimal gestational weight gains (optGWG) on our population could have an effect on the incidence of late-onset preeclampsia (LOP).Design18.5-year-observational cohort study (2001–2019).SettingsCentre Hospitalier Universitaire Hospitalier Sud Reunion’s maternity (French overseas department, Indian Ocean), the only maternity providing services to take care of all preeclamptic cases in an area with approximately 360 000 inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Importantly, we have recently demonstrated that having a high BMI does not automatically translate in a high risk of term preeclampsia. Obese patients can significantly decrease their risks by fine tuning of their gestational weight gain (GWG) [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have recently demonstrated that having a high BMI does not automatically translate in a high risk of term preeclampsia. Obese patients can significantly decrease their risks by fine tuning of their gestational weight gain (GWG) [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…First, in overweight/obese women, we may have much to win from reducing weight gain during pregnancy: significant health (and cost) benefits by lowering c-section rates, term preeclampsia, macrosomic/LGA babies, and probably gestational diabetes mellitus [ 19,20]. Second, and on the other hand, in lean women lower the rates of SGA and low-birthweights babies (< 2500g) [19].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently retrospectively tested the effect of achieving optGWG (± 2kg) in our reunionnese population by a mathematical simulation on a 18 -year (2001-2018) [15] and 19-year historical cohort. (2001-2019) [16] on 57,000, and then 59,000 term pregnancies.…”
Section: Lowering Important Maternal/fetalmentioning
confidence: 99%